2022
DOI: 10.1097/md.0000000000030959
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal infectious diseases increase the risk of psychiatric disorders: A nationwide population-based cohort study

Abstract: Intestinal infectious diseases (IIDs) are among the most common diseases and are prevalent worldwide. IIDs are also one of the major disease groups with the highest incidence worldwide, especially among children and older adults. We observed a higher probability of IIDs in patients from the psychiatric department of Tri-Service General Hospital. Therefore, our objective was to investigate if there is an association between IIDs and the risk of developing psychiatric disorders. This nationwide populationbased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…In the current study, enteric infections were negatively associated with the incidence of BD, and decreases in the incidence of enteric infections were associated with increases in both mood disorders, but more specifically with BD. These results are at variance with those of an earlier study, which found that intestinal infections were associated with an increase in subsequent mood disorders [ 76 ]. However, it is possible that variations in the incidence of enteric infections may be associated with variations in “non-pathogenic” components of the gut microbiota, which can influence symptomatology and treatment response in BD [ 154 , 155 ].…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…In the current study, enteric infections were negatively associated with the incidence of BD, and decreases in the incidence of enteric infections were associated with increases in both mood disorders, but more specifically with BD. These results are at variance with those of an earlier study, which found that intestinal infections were associated with an increase in subsequent mood disorders [ 76 ]. However, it is possible that variations in the incidence of enteric infections may be associated with variations in “non-pathogenic” components of the gut microbiota, which can influence symptomatology and treatment response in BD [ 154 , 155 ].…”
Section: Discussioncontrasting
confidence: 90%
“…However, this study’s findings were not specific to mood disorders: elevated rates of subsequent diagnoses of autism spectrum disorder, attention-deficit/hyperactivity disorder, and obsessive-compulsive disorder were also associated with bacterial infection in this sample. A larger study from the same country, including both children and adults and focusing exclusively on intestinal infections, reported similar results; intestinal infections were associated non-specifically with a wide range of mental disorders, including a 1.5–2-fold increase in mood disorder risk [ 76 ]. This non-specific pattern of association was also observed in a study from the United States, where childhood infections were not only associated with an increased risk of MDD but also of anxiety disorders and oppositional-defiant disorder (ODD) [ 56 ].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, this study's findings were not specific to mood disorders: elevated rates of subsequent diagnoses of autism spectrum disorder, attentiondeficit/hyperactivity disorder, and obsessive-compulsive disorder were also associated with bacterial infection in this sample. A larger study from the same country, including both children and adults and focusing exclusively on intestinal infections, reported similar results; intestinal infections were associated non-specifically with a wide range of mental disorders, including a 1.5-2-fold increase in mood disorder risk [76]. This non-specific pattern of association was also observed in a study from the United States, where childhood infections were not only associated with an increased risk of MDD but also of anxiety disorders and oppositional-defiant disorder (ODD) [56].…”
Section: Comparisons With the Existing Literaturementioning
confidence: 61%